Valuing the impact of residential photovoltaics and batteries on network electricity losses: An Australian case study. (October 2019) - Shaw-Williams, Damian; Susilawati, Connie; Walker, Geoff; Varendorff, Jeremy
Abstract: The transition to decentralised energy networks incorporating high levels distributed generation is the greatest network challenge since their formation. The eager adoption of photovoltaics by households is accelerating this change; the addition of residential batteries provide the next step in the process. The costs of the transition must be considered in a comprehensive evaluation of how value in the network is affected. A little considered aspect to date is the financial impact of network loss reduction resulting from generation being located at the point of load. Using an Australian case study, this paper seeks to value the reduction of network losses, the degree to which all consumers benefit, and verify the impact of PV and batteries on the LV network through power-flow modelling and comprehensive economic evaluation. This paper finds that losses can be reduced by up to 78% with the addition of batteries to manage evening peak and provide load support. Highlights: Inclusion of PV have reduced loss factors on Low-Voltage networks. The threshold for PV penetration reduction losses is 25%–50%. The addition of batteries can significantly reduce LV losses further. The cost of incentive schemes must compared to systemic benefits.